2022
DOI: 10.3389/fnut.2022.850109
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Total Protein Intake and All-Cause Mortality in Middle Aged and Older Korean Adults With Chronic Kidney Disease

Abstract: Background and AimsOver the past decades, the optimum protein intake for patients with chronic kidney disease (CKD) has been an important, controversial issue. Dietary protein restriction has been commonly recommended for patients with CKD for preserving kidney function. However, evidence of the associations between long-term protein intake and mortality is not consistent in patients with CKD. Therefore, we aimed to examine the associations between total protein intake and all-cause mortality in Korean adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(77 reference statements)
1
3
0
Order By: Relevance
“…Results of this multicohort study are in line with those of observational studies [10][11][12] that have found neutral or inverse associations between protein intake and mortality among older persons with CKD stages 3 to 5 not receiving dialysis. First, in 3892 middle aged and older Korean adults, higher total protein intake showed a null association with 11-year all-cause mortality.…”
Section: Discussion Interpretationsupporting
confidence: 89%
See 2 more Smart Citations
“…Results of this multicohort study are in line with those of observational studies [10][11][12] that have found neutral or inverse associations between protein intake and mortality among older persons with CKD stages 3 to 5 not receiving dialysis. First, in 3892 middle aged and older Korean adults, higher total protein intake showed a null association with 11-year all-cause mortality.…”
Section: Discussion Interpretationsupporting
confidence: 89%
“…First, in 3892 middle aged and older Korean adults, higher total protein intake showed a null association with 11-year all-cause mortality. 10 Second, among 356 French patients with CKD over 60 years, higher total protein intake was not associated with increased mortality after 3 years. 12 Third, in 259 Japanese adults with CKD and older than 65 years, higher total protein intake was associated with lower risk of all-cause death over 4 years, although participants had been advised to limit protein intake depending on their CKD stage.…”
Section: Discussion Interpretationmentioning
confidence: 89%
See 1 more Smart Citation
“…68 Fourth, all OC patients used in our study were Chinese; it might be difficult for our findings to be generalized to populations with different racial and socio-economic distributions because dietary habits, food selections, and cooking methods between various populations may differ. 69 Fifth, our study explored the relationship between dietary choline before diagnosis and OC prognosis, without exploring the effect of dietary choline after diagnosis. Future studies should consider this issue.…”
Section: Discussionmentioning
confidence: 99%